2008
DOI: 10.1007/s00572-008-0180-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of arbuscular mycorrhizae on photosynthesis and water status of maize plants under salt stress

Abstract: The influence of arbuscular mycorrhizal (AM) fungus Glomus mosseae on characteristics of the growth, water status, chlorophyll concentration, gas exchange, and chlorophyll fluorescence of maize plants under salt stress was studied in the greenhouse. Maize plants were grown in sand and soil mixture with five NaCl levels (0, 0.5, 1.0, 1.5, and 2.0 g/kg dry substrate) for 55 days, following 15 days of non-saline pretreatment. Under salt stress, mycorrhizal maize plants had higher dry weight of shoot and root, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
341
4
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(422 citation statements)
references
References 34 publications
60
341
4
17
Order By: Relevance
“…These findings are in agreement with other researchers working on different vegetable crops, who reported that salinity not only affects the host plant growth but also the AM fungi colonization [2,[6][7][8]. Salinity can reduce AM colonization capacity, spore germination and inhibiting growth of hyphae of the fungus [12,22,23]. These reports have indicated that the negative effects of salinity on the AM fungus probably due to the direct effect of present salts on the fungi [22,24].…”
Section: Mycorrhizal Colonizationsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with other researchers working on different vegetable crops, who reported that salinity not only affects the host plant growth but also the AM fungi colonization [2,[6][7][8]. Salinity can reduce AM colonization capacity, spore germination and inhibiting growth of hyphae of the fungus [12,22,23]. These reports have indicated that the negative effects of salinity on the AM fungus probably due to the direct effect of present salts on the fungi [22,24].…”
Section: Mycorrhizal Colonizationsupporting
confidence: 92%
“…Inoculation of transplants prior to salt exposure might help bypassing the potential inhibitory effects that salt could have on AM fungal spore germination. Such inhibitory effects of salinity on rate of mycorrhizal colonization have been reported [12,22,23]. The procedure used in this study of pre-inoculating transplant seedlings with AM fungi can be of practical importance in the cultivation of many horticultural crops grown under saline conditions.…”
Section: Mycorrhizal Enhancement Effectmentioning
confidence: 67%
“…Salinity significantly depressed G. mosseaecolonization but not P. occultum-colonization, implying that fungal species provide a different capacity to respond to salinity. This is in agreement with several studies on maize 15 and zucchini 16 . Salinity has been shown to decrease growth characteristics of citrus seedlings in saline soils ( Table 1).…”
Section: Resultssupporting
confidence: 94%
“…From the present investigation, it was clearly observed that the dark adapted quantum yield (F v /F m ratio), performance index (PI abs ), photochemical quenching (qP) and stomatal conductance (g s ) were decreased with the increase in salinity concentration but increased by Th application. This could be due to an increase in chlorophyll concentration by the application of Trichoderma in saline environment (Sheng et al 2008).…”
Section: Discussionmentioning
confidence: 99%